The transmedia lies of Pinocchio: morality and intertextuality in the narra-tive expansion of Carlo Collodi's tale - Freire-Sánchez, Alfonso (2025)
This research explores the narrative universe of Pinocchio through an analytical approach that adapts the model proposed by García-Carrizo and Heredero-Díaz (2015), identifying the transmedia dynamics that have sustained the relevance and evolution of the original story across multiple formats and media. The main findings highlight how key narrative elements and mythemes, such as the myth of Prometheus, have been reinterpreted and re-signified over time, preserving the identity of the tale despite the diversity of adaptations. Furthermore, the study examines how these adaptations have altered and, in some cases, subverted the original moralizing values and pedagogical precepts, reflecting the cultural and social transformations of the past 140 years. Based on Carlo Collodi's classic tale Le avventure di Pinocchio. Storia di un burattino (1883), a paradigmatic case of transmedia archaeology, our study revisits the concept of transmedia intertextuality to understand how these connections enable the expansion and re-signification of original works, maintaining their relevance in new cultural contexts and establishing a methodological framework applicable to other studies of transmedia narratives.